Natural Hydroxyapatite: Green Catalyst for the Synthesis of Pyrroles, Inhibitors of Corrosion - Abdelhadi Louroubi; Abdallah Nayad; Ali Hasnaoui; Rachid Idouhli; Abdessalam Abouelfida; Larbi El Firdoussi; Mustapha Ait Ali (Journal of Chemistry)
Polysubstituted pyrroles have been synthesized in good yields via a four-component one-pot reaction of 1,3-dicarbonyl compounds, amines, aldehydes, and nitroalkanes using natural hydroxyapatite (HAp) as an efficient green catalyst. This strategy provides advantages such as simple experimental and work-up procedures, mild conditions, high selectivity, low cost, high atom economy, and environmental friendliness; it uses a green commercial catalyst and does not require a solvent. The electrochemical behavior of S300 steel in 1 M hydrochloric acidic was studied in the presence of these heterocyclic compounds. The results showed good inhibition efficiency for steel in acidic media.